2011
DOI: 10.1029/2011gl048366
|View full text |Cite
|
Sign up to set email alerts
|

An alternate and robust approach to calibration for the estimation of land surface model parameters based on remotely sensed observations

Abstract: [1] Atmospheric models include land surface parameterizations of heat and moisture fluxes. Most parameterizations derive from early models of layered soil and vegetation canopy that account for liquid, vapor and heat diffusion, radiation processes, and surface turbulence. The number of parameters in these models ranges roughly from 10 to 50. Some parameters are known to vary over a small range and/or not significantly impact predictions. Others are highly influential (e.g., Leaf Area Index), but are currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It has been demonstrated that batch calibration using soil moisture can result in a better match between modelled and observed soil moisture [139]. However, these studies focused on improved surface or root-zone soil moisture simulation through either conceptual models or physically-based models [138,[140][141][142][143]. From the flood forecasting perspective, a more important question is how the batch calibration using soil moisture affects the streamflow simulation/forecasting.…”
Section: Batch Calibrationmentioning
confidence: 99%
“…It has been demonstrated that batch calibration using soil moisture can result in a better match between modelled and observed soil moisture [139]. However, these studies focused on improved surface or root-zone soil moisture simulation through either conceptual models or physically-based models [138,[140][141][142][143]. From the flood forecasting perspective, a more important question is how the batch calibration using soil moisture affects the streamflow simulation/forecasting.…”
Section: Batch Calibrationmentioning
confidence: 99%
“…The PTF approach is used in the present paper. It is important, however, to acknowledge the existence of other approaches to estimating SHPs, including those utilizing remotely sensed soil moisture retrievals [Santanello et al, 2007;Pauwels et al, 2009;Salvucci and Entekhabi, 2011;Harrison et al, 2012]. This type of approach (not discussed further here) comes with its own set of issues; the retrievals, for example, inherently include some assumption about soil texture, which may be inconsistent with the texture assumed in the land surface model, and the optimized SHP values and the feasibility of a global calibration effort will depend on the choice of the calibration algorithm and on the coverage and quality of the remote sensing data.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling outcomes may then deviate significantly from reality in areas where the land cover type does not change but its energetic and hydrological function is different from that bulk, categorical representation [Law et al, 2002]. Remote sensing-based phenology can be incorporated directly into the calculations of the LSMs that are coupled with regional weather and climate modeling systems [Sellers et al, 1996;Bonan et al, 2002;Sterling and Ducharne, 2008] and provide verisimilitude to the modeled vegetation biophysical traits including seasonal maxima of albedo, leaf area index (LAI), and stomatal conductance [Dorman and Sellers, 1989;Salvucci and Entekhabi, 2011].…”
Section: Orientation On Land-atmosphere Interactions and Modelingmentioning
confidence: 99%